Perceptions of people on police efficiency and crime prevention in urban areas in Malaysia - Ishak, Suryati (David Publishing, 2016)
Crime cases from snatch thefts to murders, are becoming increasingly common in Malaysia according to the database of the Royal Malaysian Police (RMP), the current overall Crime Index in Malaysia was 147,062 for 2013 compared with 65,237 in 1977. The database also revealed that the number of property crimes reported in this country has always exceeded the number of violent crimes. Although in 2013, crimes related to property are higher(117,687) than violent crime (29,375), the gradual increase in the latter does worry Malaysians. Likewise,Malaysian Government had implemented a “safe community” concept, inspired by the Malaysian Crime Prevention Foundation (MCPF), a non-government organization, as they were concerned that the threat of violent crime and non-violent crime would eventually reduce the quality of life for many individuals. The concept is very important to the public as it is perceived as improved safety for the public with less crime. This study analyzes the public safety through their perceptions on the effectiveness of the policeman and suggesting few prevention actions against crime. The data were collected using a self-administered survey questionnaire. Specifically, this study focuses on the more developed states in this country. From the cross tabulation analysis, the majority of respondents agreed that the police are effective in controlling crime. Approximately, 72.1% of respondents felt that the police are efficient in controlling crime.